2006
DOI: 10.1681/asn.2006080927
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment with Calcimimetics on Hyperparathyroidism and Vascular Mineralization

Abstract: Soft tissue calcification that involves primarily the medial portion of the arterial vasculature is a widely recognized and common complication of chronic kidney disease Vascular calcification (VC) causes increased arterial stiffness and contributes to the high cardiovascular mortality and morbidity in dialysis patients. The pathogenesis of VC is complex and includes factors that promote calcification and others that inhibit calcification. Studies in dialysis patients have shown a correlation between VC and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…In an animal study, PTX can reverse increased pulmonary calcification and reduce pulmonary hypertension [32]. In a small-scale human study, similar results of decreased arterial stiffness have been noted after treatment with a calcimimetic agent [3,20]. …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In an animal study, PTX can reverse increased pulmonary calcification and reduce pulmonary hypertension [32]. In a small-scale human study, similar results of decreased arterial stiffness have been noted after treatment with a calcimimetic agent [3,20]. …”
Section: Discussionmentioning
confidence: 82%
“…Parathyroidectomy (PTX) is reserved for medically refractory SHPT. Drastic reductions in PTH and phosphate levels after PTX may lead to improved blood pressure (BP) and arterial stiffness [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Amongst these risk factors, hyperphosphatemia is an especially strong and independent predictor of cardiovascular mortality in uremic patients [39] . Treatment of secondary hyperparathyroidism and hyperphosphatemia with calcimimetics might have beneficial effects for the vascular mineralization and mortality in CKD, an effect that can be at least be partly mediated through the reduction of arterial stiffness [42] . For many years, VC in CKD patients was thought to occur predominantly by unregulated, purely physiochemical mechanisms [43] .…”
Section: Vascular Calcification In Ckdmentioning
confidence: 99%
“…The related mineral and bone disorders are early onset, common and serious complications because of their significant impact on morbidity and mortality due to skeletal (renal osteodystrophy, loss of bone mineral density, bone pain, and fractures) and extra skeletal manifestations particularly cardiovascular manifestations 2,3 . Conventional treatment with a calcium supplement, phosphate binders and active vitamin D derivatives lead in part to amelioration of secondary hyperparathyroidism, but are simultaneously associated with unacceptable side-effects, including hypercalcemia, hyperphosphatemia, and increased calcium-phosphate products Recent approaches to its management include calcimimetics which are drugs increasing the activity of the calcium-sensing receptor by enhancing allosterically the action of calcium ions at this receptor 4,5,6,7 .…”
mentioning
confidence: 99%
“…In contrast to the effect of active vitamin D derivatives, cinacalcet simultaneously decreases calcium, phosphate and calcium-phosphate product levels 4,11,12 . Additionally, some studies have shown that cinacalcet reduce the risk of vascular calcification, parathyroidectomy, bone fracture, cardiovascular hospitalisation and decrease parathyroid hyperplasia among long-term dialysis patients with secondary hyperparathyroidism 2,4,11,13 .…”
mentioning
confidence: 99%